2013
DOI: 10.5801/ncn.v16i1.1193
|View full text |Cite
|
Sign up to set email alerts
|

Caminhos cruzados: relação entre empresa, trabalhadores e sindicato em Polo oleiro-cerâmico da Região Metropolitana de Manaus-AM

Abstract: ResumoO presente artigo é fruto da pesquisa do mestrado em Sociologia na Universidade do Amazonas, de 2011 a 2013, e analisa a relação entre empresa, trabalhadores e sindicatos no Polo oleiro-cerâmico da Região Metropolitana de Manaus, setor que fabrica 75% dos tijolos e telhas consumidos no Amazonas. A ideia central deste trabalho é mostrar quais são as principais estratégias empresariais empreendidas pelo dono da olaria investigada, bem como traçar um perfi l dos trabalhadores oleiros. Além disso, busca-se r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Starting Even in light of the many obstacles and technological limitations confronted by the sector, research has shown that between 2009 and 2010, the ceramic industry of the State of Amazonas generated between 3.5 and four thousand jobs, directly and indirectly, with an estimated production of 35 tons of bricks/month, with Iranduba and Manacapuru being the principal producers of red ceramics. The city of Iranduba alone was responsible for about 75% the entire production of bricks and roof tiles in the State [36].…”
Section: Resultsmentioning
confidence: 99%
“…Starting Even in light of the many obstacles and technological limitations confronted by the sector, research has shown that between 2009 and 2010, the ceramic industry of the State of Amazonas generated between 3.5 and four thousand jobs, directly and indirectly, with an estimated production of 35 tons of bricks/month, with Iranduba and Manacapuru being the principal producers of red ceramics. The city of Iranduba alone was responsible for about 75% the entire production of bricks and roof tiles in the State [36].…”
Section: Resultsmentioning
confidence: 99%
“…It has been estimated that at the height of the real estate boom in Brazil between 2008 and 2013 the annual production of ceramics in Amazonas was approximately 35 tons of bricks per month, with the cities of Iranduba and Manacapuru being the principal producers of red ceramics. Just the city of Iranduba was responsible for about 75% of all brick production in the state, producing between 1700 and 2000 direct and indirect jobs [18,30].…”
Section: Geographic and Geologic Aspects Of The Study Areamentioning
confidence: 99%